1972
DOI: 10.2307/2346598
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Non-Normality on the Distribution of the Sample Product-Moment Correlation Coefficient

Abstract: Samples from non-normal bivariate distributions are simulated and the densities of the sample product-moment correlation coefficient, r, estimated and compared with the corresponding normal theory densities. The results are contrasted with the literature on the subject and an attempt is made to reconcile some of the earlier conflictingconclusions regarding the robustness of the distribution of r.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 28 publications
4
116
1
Order By: Relevance
“…Kowalski, 1972;Habib et al, 2001;Serinaldi, 2008). In our case, the Gaussian distribution does not seem to describe very well the distribution of the random errors at short time-scales, while it is a reasonably good approximation at hourly and three-hourly scales.…”
Section: Random Componentcontrasting
confidence: 62%
“…Kowalski, 1972;Habib et al, 2001;Serinaldi, 2008). In our case, the Gaussian distribution does not seem to describe very well the distribution of the random errors at short time-scales, while it is a reasonably good approximation at hourly and three-hourly scales.…”
Section: Random Componentcontrasting
confidence: 62%
“…Increasing the sample size does not eliminate the bias; indeed, it can actually exacerbate the problems produced by heteroskedasticity when using OLSE (Hayes, 1996;Long & Ervin, 2000). Although it is largely impossible to construct generalizable rules about the extent to which inferences from OLS regression are going to be affected by heteroskedasticity, the existing literature provides some guidance (e.g., Duncan & Layard, 1973;Edgell & Noon, 1984;Hayes, 1996;Kowalski, 1973;Long & Ervin, 2000;Rasmussen, 1989). First, relatively mild heteroskedasticity is not going to produce profound problems and is unlikely to swing the outcome of an analysis drastically one way or the other.…”
Section: What Is Heteroskedasticity and What Are Its Effects On Infermentioning
confidence: 99%
“…However, the Pearson correlation coefficient is not robust to violations of the assumption of normality (e.g. Bishara & Hittner, 2012;Kowalski, 1972), and Osborne (2010) suggested that correlational analyses…”
Section: Distributions Of the Indicesmentioning
confidence: 99%